Analysis of carbon bonds regulatory framework and indigenous rights in Andean countries - Jaimes-Becerra, Jesús Ramón; Villegas-Solís, Jenny Marlene; García-Quezada, Génesis Andrea; Campaña-Chaglla, Jimena Alexandra (IUSTITIA SOCIALIS, 2025)
This study presents a comparative analysis of the regulatory framework and implementation of carbon bonds in the member countries of the Andean Community of Nations, CAN (Colombia, Peru, Ecuador, and Bolivia). The research identifies distinctive patterns in the regulations of each member country. Through social events analysis (lawsuits, popular consultations and protests), common challenges are identified, especially regarding prior consultation with indigenous peoples. The study concludes that, despite different national approaches, there is significant potential for regional cooperation and harmonization of standards while respecting human rights. The development of common protocols and the implementation of transparent registration and monitoring systems are recommended. This research contributes to understanding regional dynamics in carbon market development, facilitating more effective participation in them